Ionic solvent film, alkaline water electrolytic bath device, preparation method and application

By blending sulfonated cellulose with polybenzimidazole and heat treatment and deprotonation, an ion solvent film with high ion conductivity and mechanical strength was prepared, which solved the problem that existing membrane materials could not have both performances and achieved excellent performance in alkaline electrolytic water systems.

CN119640329APending Publication Date: 2025-03-18BEIJING YUANTAI ENERGY MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411784527.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing ionic solvent films cannot have both high ion conductivity and mechanical strength, which limits their application in alkaline electrolytic water systems.

Method used

By blending sulfonated cellulose with polybenzimidazole and subjecting heat treatment and deprotonation treatment, an ionic solvent film with excellent mechanical properties and high ion conductivity was prepared.

Benefits of technology

The prepared ionic solvent film not only performs excellently in terms of mechanical strength and conductivity, but also has good alkali stability and electrolytic properties, and is suitable for alkaline electrolytic water systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640329A_ABST
    Figure CN119640329A_ABST
Patent Text Reader

Abstract

The invention discloses an ionic solvent membrane, an alkaline water electrolytic bath device, a preparation method and application. The preparation method of the ionic solvent membrane comprises the following steps: mixing cellulose and a sulfonating agent for first reaction, adding first alkali liquor to adjust the pH value of the solution to 6.5-7.5, and preparing sulfonated cellulose; dissolving sulfonated cellulose in an organic solvent, mixing with polybenzimidazole, and carrying out a second reaction to prepare a film; and placing the prepared membrane in a second alkali liquor for deprotonation to prepare the ionic solvent membrane. The prepared ionic solvent film has better hydrophilicity and better mechanical properties, and is high in ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of alkaline water electrolysis anion exchange membranes, and relates to an ion solvent membrane, an alkaline water electrolysis cell device, a preparation method and an application. Background Art

[0002] Introducing ion solvent membranes in alkaline electrolyzer systems to electrolyze water to produce hydrogen can achieve efficient energy conversion. For example, by coupling wind farms and photovoltaic power stations with water electrolysis systems, excess green electricity can be converted into green hydrogen, achieving long-term energy storage. This semi-solid membrane of the solid-liquid binary system contains polymers with hydrophilic groups and alkaline solutions, combining the gas barrier properties of dense polymer films and the conductivity of alkaline solution electrolytes. However, current ion solvent membranes cannot combine high ion conductivity and mechanical strength. Summary of the invention

[0003] In view of the problem of unbalanced ion conductivity and mechanical strength of current ion solvent membranes, the present invention provides an ion solvent membrane, an alkaline water electrolyzer device, a preparation method and applications.

[0004] In some embodiments, a method for preparing an ionic solvent membrane is provided, comprising the following steps:

[0005] The sulfonated cellulose, an organic solvent and polybenzimidazole are mixed to prepare a casting solution, and the casting solution is heat-treated to form a film by casting;

[0006] The membrane formed by casting is deprotonated to prepare the ion solvent membrane.

[0007] In some embodiments, in the method for preparing an ionic solvent membrane provided, the mass ratio of the sulfonated cellulose to the polybenzimidazole is (5-20): (80-95) based on the feed amount.

[0008] In some embodiments, in the method for preparing an ionic solvent membrane provided, in the casting solution, the mass volume ratio of the total mass of sulfonated cellulose and polybenzimidazole to the organic solvent is (5-10) g:100 mL, calculated by the feed amount.

[0009] In some embodiments, the method for preparing an ionic solvent membrane provides one or more of the following features:

[0010] The polybenzimidazole comprises one or more of poly(2,5-benzimidazole), poly(2,2'-phenyl-5,5'-benzimidazole), poly(2,2'-(m-phenyl)-5,5'-benzimidazole), pyridine bridged polybenzimidazole and poly(4,4'-diphenyl ether-5,5'-benzimidazole);

[0011] The weight average molecular weight of the polybenzimidazole is 80 kDa to 100 kDa;

[0012] The organic solvent comprises one or more of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.

[0013] In some embodiments, in the method for preparing an ionic solvent membrane provided, the method for preparing sulfonated cellulose comprises the following steps: mixing cellulose with a sulfonating agent for sulfonation reaction, adjusting the pH value to 6.5-7.5, to prepare the sulfonated cellulose;

[0014] In some embodiments, in the method for preparing an ionic solvent membrane provided, the method for preparing sulfonated cellulose satisfies one or more of the following characteristics:

[0015] The ratio of the cellulose to the sulfonating agent is 1 g: (5-10) mL;

[0016] The weight average molecular weight of the cellulose is 30 kDa to 100 kDa;

[0017] The cellulose comprises one or more of microcrystalline cellulose, cellulose nanocrystals, bacterial cellulose and cellulose nanofibers;

[0018] The sulfonating agent comprises one or more of sulfuric acid, chlorosulfonic acid, sulfur trioxide, aminosulfonic acid and sulfite;

[0019] The sulfonating agent is added in the form of a sulfonating agent aqueous solution, and optionally, the sulfonating agent aqueous solution contains water and the sulfonating agent at a volume percentage concentration of 40% to 60%;

[0020] The temperature for carrying out the sulfonation reaction is 5°C to 30°C;

[0021] The sulfonation reaction is carried out for 6 h to 12 h.

[0022] In some embodiments, the method for preparing an ionic solvent membrane provides one or more of the following features:

[0023] The temperature for the heat treatment is 100°C to 130°C;

[0024] The heat treatment is performed for 6 h to 24 h.

[0025] In some embodiments, the method for preparing an ionic solvent membrane provides one or more of the following features:

[0026] In the step of casting the film, the product obtained by heat treatment is cast on a substrate, and vacuum dried at 60° C. to 100° C. for 24 h to 36 h to form a film;

[0027] In the step of performing the deprotonation, alkaline solution is used for deprotonation, and the alkaline solution is a 20wt%~50wt% KOH solution.

[0028] In some embodiments, an ion solvent membrane is provided, which is prepared by the preparation method.

[0029] In some embodiments, there is provided a use of the ionic solvent membrane in alkaline water electrolysis or in a device for preparing alkaline water electrolysis.

[0030] In some embodiments, an alkaline water electrolysis device is provided, comprising an alkaline electrolyzer system, wherein the alkaline electrolyzer system comprises the ion solvent membrane.

[0031] The preparation method of the ion solvent membrane provided by the present invention uses microcrystalline cellulose as a reinforcing material, uses a sulfonating agent to modify the cellulose, functionalizes the cellulose main chain with sulfonic acid, and blends with polybenzimidazole to prepare the ion solvent membrane. The prepared ion solvent membrane has better hydrophilicity and better mechanical properties, and high ion conductivity. The prepared ion solvent membrane is applied to alkaline water electrolysis to have good water electrolysis performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the implementation methods and examples of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for use in the description of the implementation methods or examples. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0033] Figure 1 is a flow chart of the preparation of an ionic solvent membrane in one embodiment;

[0034] Figure 2 The polarization curves of the polymer obtained in step (3) of Example 1, Example 2 and Comparative Example 1 in alkaline electrolyzed water are shown in FIG. DETAILED DESCRIPTION

[0035] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0037] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0038] In the present application, "plurality", "multiple", "multiple times", "multiples", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0039] The terms "combination thereof", "any combination thereof", "any combination thereof" and the like used in this application include all suitable combinations of any two or more of the listed items.

[0040] In this application, the "suitable" mentioned in "suitable combination", "suitable method", "any suitable method", etc. is based on the ability to implement the technical solution of this application, solve the technical problems of this application, and achieve the expected technical effects of this application.

[0041] In the present application, "preferred", "better", "more preferred" and "suitable" are only used to describe implementation methods or examples with better effects. It should be understood that they do not constitute limitations on the scope of protection of the present application.

[0042] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0043] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0044] In the present invention, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0045] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0046] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1 to 10, indicating that t is any integer selected from the group of integers consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges included therein.

[0047] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0048] In the present application, % (w / w) and wt% both represent weight percentage, % (v / v) refers to volume percentage, and % (w / v) refers to mass volume percentage.

[0049] The "room temperature" in this application generally refers to 5°C to 30°C, preferably 25±5°C.

[0050] As a highly efficient means of energy conversion, water electrolysis technology is becoming increasingly important. By coupling wind farms and photovoltaic power stations with water electrolysis systems, excess green electricity can be converted into green hydrogen, which not only realizes long-term energy storage, but also effectively alleviates the phenomenon of wind and solar power abandonment. Proton exchange membrane (PEM) water electrolysis technology, based on the perfluorosulfonic acid membrane it uses, demonstrates excellent electrocatalytic efficiency and high purity characteristics of the output gas. However, due to its reliance on precious metals such as platinum, iridium, and ruthenium as catalysts, its large-scale commercialization is subject to certain constraints. Relatively speaking, traditional alkaline water electrolysis technology is superior in cost-effectiveness and durability because it can use more economical and more stable non-precious metal catalysts in alkaline media, and therefore shows a wider range of applicability prospects.

[0051] In addition, the anion exchange membrane (AEM) electrolyzer technology, which has developed rapidly in recent years, combines the advantages of proton exchange membrane (PEM) and traditional alkaline electrolyzer, showing its potential as the next generation of low-cost, high-efficiency water electrolysis hydrogen production technology. However, the current anion exchange membrane based on quaternary ammonium salt functionalization has the problem of insufficient stability, which limits its ability to operate continuously for a long time, and thus still faces significant technical challenges in meeting industrial application standards.

[0052] Another feasible idea is to introduce ion solvent membrane into the alkaline electrolyzer system. This semi-solid membrane of solid-liquid binary system is composed of polymers containing hydrophilic groups and alkaline solutions, such as polybenzimidazole-potassium hydroxide solution ion solvent membrane, which combines the gas barrier properties of dense polymer films and the conductivity of alkaline solution electrolytes. However, current ion solvent membranes cannot combine high ion conductivity and mechanical strength.

[0053] Although ion solvent membranes can theoretically provide good ion conductivity, one of the key issues is how to design membrane materials with both high ion conductivity and mechanical strength. Common improvement methods involve the design of new monomers, cross-linking and organic-inorganic composites, all of which are relatively complex processes.

[0054] In some embodiments, a method for preparing an ionic solvent membrane is provided, comprising the following steps:

[0055] The sulfonated cellulose, organic solvent and polybenzimidazole are mixed to prepare a casting solution, the casting solution is heat-treated, and then cast into a film;

[0056] The membrane formed by casting is deprotonated to prepare an ion solvent membrane.

[0057] Cellulose, as a naturally occurring polymer material, has good mechanical strength and toughness. At the same time, cellulose molecules contain a large number of hydroxyl groups (-OH), which can participate in the formation of hydrogen bonds to improve the mechanical properties of the film. At the same time, sulfonation treatment can also increase the hydrophilicity of the film.

[0058] In some embodiments, a method for preparing an ionic solvent membrane is provided, comprising the following steps:

[0059] S100: mixing sulfonated cellulose, an organic solvent and polybenzimidazole to prepare a casting solution, heat-treating the casting solution, and casting into a film;

[0060] S200: Deprotonate the film formed by casting to prepare an ion solvent membrane. The preparation process of the ion solvent membrane preparation method provided is as follows: Figure 1 shown.

[0061] In some embodiments, in the method for preparing an ionic solvent membrane, in step S100, based on the amount of feed, the mass ratio of sulfonated cellulose to polybenzimidazole is (5-20):(80-95), for example, 5:95, 6:94, 7:93, 8:92, 9:91, 10:90, 11:89, 12:88, 13:87, 14:86, 15:85, 16:84, 17:83, 18:82, 19:81, 20:80 or a range selected from any two of the foregoing ratios.

[0062] In some embodiments, in the method for preparing an ionic solvent membrane, in step S100, in the casting solution, based on the feed amount, the mass volume ratio of the total mass of sulfonated cellulose and polybenzimidazole to the mass volume ratio of the organic solvent is (5~10) g:100 mL. For example, the mass volume ratio of the total mass of sulfonated cellulose and polybenzimidazole to the organic solvent is 5 g:100 mL, 6 g:100 mL, 7 g:100 mL, 8 g:100 mL, 9 g:100 mL, 10 g:100 mL or a range selected from any two of the foregoing ratios.

[0063] In some embodiments, in the method for preparing an ionic solvent membrane, in step S100, the polybenzimidazole includes one or more of poly(2,5-benzimidazole) (AB-PBI), poly(2,2'-phenyl-5,5'-benzimidazole) (PBI-4 N), poly(2,2'-(m-phenyl)-5,5'-benzimidazole) (m-PBI), pyridine-bridged polybenzimidazole (Py-PBIs), and poly(4,4'-diphenyl ether-5,5'-benzimidazole) (OPBI).

[0064] In some embodiments, the polybenzimidazole is poly(2,2'-(m-phenyl)-5,5'-benzimidazole).

[0065] In some embodiments, the method for preparing poly(2,2'-(m-phenyl)-5,5'-benzimidazole) comprises the following steps:

[0066] In the presence of a solvent, the aromatic tetraamine and the aromatic diacid undergo a condensation reaction, the temperature of the condensation reaction is 150°C~200°C, the time is 4h~24h, and the molar ratio of the aromatic tetraamine and the aromatic diacid is (1~3): (1~3).

[0067] In some embodiments, in the method for preparing poly(2,2'-(m-phenyl)-5,5'-benzimidazole), the solvent comprises polyphosphoric acid.

[0068] In some embodiments, in the preparation method of poly(2,2'-(m-phenyl)-5,5'-benzimidazole), in order to improve the polycondensation effect, before the polycondensation reaction occurs, the solvent PPA can be heated to 120°C~150°C under stirring and nitrogen atmosphere, and maintained at 120°C~150°C for 30min~60min to remove moisture from polyphosphoric acid (PPA).

[0069] In some embodiments, in the method for preparing an ionic solvent membrane, in step S100, the weight average molecular weight of the polybenzimidazole is 80 kDa to 100 kDa.

[0070] In some embodiments, in the method for preparing an ionic solvent membrane, in step S100, the organic solvent comprises one or more of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0071] In some embodiments, in the method for preparing an ion solvent membrane, the method for preparing sulfonated cellulose comprises the following steps: mixing cellulose with a sulfonating agent for sulfonation reaction, and adjusting the pH value to 6.5-7.5 to prepare sulfonated cellulose.

[0072] In some embodiments, in the method for preparing an ionic solvent membrane, in the method for preparing sulfonated cellulose, the ratio of cellulose to the sulfonating agent is 1 g: (5~10) mL, based on the feed amount. For example, the ratio of cellulose to the sulfonating agent can be 1 g: 5 mL, 1 g: 6 mL, 1 g: 7 mL, 1 g: 8 mL, 1 g: 9 mL, 1 g: 10 mL, or a range selected from any two of the foregoing ratios.

[0073] In some embodiments, in the method for preparing an ionic solvent membrane, in the method for preparing sulfonated cellulose, the weight average molecular weight of the cellulose is 30 kDa to 100 kDa.

[0074] In some embodiments, in the method for preparing an ionic solvent membrane, in the method for preparing sulfonated cellulose, the cellulose comprises one or more of microcrystalline cellulose, cellulose nanocrystals, bacterial cellulose, and cellulose nanofibers.

[0075] In some embodiments, in the method for preparing an ionic solvent membrane, in the method for preparing sulfonated cellulose, the sulfonating agent comprises one or more of sulfuric acid, chlorosulfonic acid, sulfur trioxide, aminosulfonic acid, and sulfite.

[0076] In some embodiments, the sulfonating agent is added in the form of an aqueous solution of the sulfonating agent.

[0077] In some embodiments, the aqueous solution of the sulfonating agent contains water and a sulfonating agent in a concentration of 40% to 60% by volume.

[0078] In some embodiments, in the preparation method of the ionic solvent membrane, in the preparation method of the sulfonated cellulose, the temperature for the sulfonation reaction is 5°C~30°C. For example, the temperature for the sulfonation reaction can be 5°C, 6°C, 7°C, 8°C, 9°C, 10°C, 11°C, 12°C, 13°C, 14°C, 15°C, 16°C, 17°C, 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C or a range selected from any two of the foregoing values.

[0079] In some embodiments, in the preparation method of the ionic solvent membrane, in the preparation method of the sulfonated cellulose, the time for the sulfonation reaction is 6h~12h. For example, the time for the sulfonation reaction can be 6h, 7h, 8h, 9h, 10h, 11h, 12h or a range selected from any two of the foregoing values.

[0080] In some embodiments, in the method for preparing an ionic solvent membrane, in the method for preparing sulfonated cellulose, in the step of adjusting the pH value to 6.5-7.5, an alkali solution is used to adjust the pH value, and the alkali solution includes one or more of KOH, NaOH, LiOH, K2CO3, Na2CO3, KHCO3 and NaHCO3 aqueous solutions.

[0081] In some embodiments, in the method for preparing an ionic solvent membrane, in the method for preparing sulfonated cellulose, after preparing the sulfonated cellulose, the method further comprises the following steps: washing the prepared sulfonated cellulose with deionized water, and vacuum drying.

[0082] In some embodiments, in the method for preparing the ionic solvent membrane, in the method for preparing sulfonated cellulose, the vacuum drying temperature is 30° C. to 100° C., and the vacuum drying time is 24 h to 36 h.

[0083] In some embodiments, in the method for preparing an ionic solvent membrane, in step S100, the temperature for heat treatment is 100°C~130°C, for example, 100°C, 101°C, 102°C, 103°C, 104°C, 105°C, 106°C, 107°C, 108°C, 109°C, 110°C, 111°C, 112°C, 113°C, 114°C, 115°C, 116°C, 117°C, 118°C, 119°C, 120°C, 121°C, 122°C, 123°C, 124°C, 125°C, 126°C, 127°C, 128°C, 129°C, 130°C or a range selected from any two of the foregoing values.

[0084] In some embodiments, in the method for preparing an ionic solvent membrane, in step S100, the time for heat treatment is 6h-24h, for example, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h or a range selected from any two of the foregoing values.

[0085] In some embodiments, in the method for preparing an ion solvent membrane, in step S100, in the step of casting the membrane, the product obtained by heat treatment is cast on a substrate (such as a glass plate), and vacuum dried at 60°C to 100°C for 24h to 36h to form a membrane.

[0086] In some embodiments, in the method for preparing an ionic solvent membrane, in step S200, in the step of deprotonating, deprotonation is performed using an alkali solution, and the alkali solution is a 20wt%~50wt% KOH solution. For example, the concentration of the KOH solution can be 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt% or a range selected from any two of the foregoing values.

[0087] In some embodiments, an ionic solvent membrane is provided, which is prepared by the aforementioned preparation method.

[0088] In some embodiments, use of an ion solvent membrane in alkaline water electrolysis or in an alkaline water electrolysis device is provided.

[0089] In some embodiments, an alkaline water electrolyzer is also provided, comprising the aforementioned ion solvent membrane.

[0090] In some embodiments, an alkaline water electrolysis device is provided, comprising an alkaline electrolyzer system, wherein the alkaline electrolyzer system comprises the aforementioned ion solvent membrane.

[0091] Understandably, the preparation method of the provided ion solvent membrane is firstly to functionalize cellulose with sulfuric acid; secondly, to add the sulfonated cellulose as a reinforcing material into the polybenzimidazole system; finally, to prepare the ion exchange membrane by a casting method and to deprotonate it to obtain a polybenzimidazole ion solvent membrane with different cellulose addition amounts. During the preparation process, the addition of sulfonated cellulose not only improves the mechanical properties of the membrane, but also promotes the increase of the hydrophilicity of the membrane and improves the ion conductivity of the film. The ion membrane prepared by the present invention exhibits excellent alkali stability, excellent mechanical strength and dimensional stability. In addition, the membrane also has higher electrical conductivity and better water electrolysis performance, which is of great significance in scientific research and industrial applications, and expands new possibilities for the application of water electrolysis technology.

[0092] The following examples further illustrate in detail the preparation method and performance of a modified cellulose-enhanced ionic solvent membrane according to the present invention.

[0093] The microcrystalline cellulose used in the examples was purchased from Northern Century (Jiangsu) Cellulose Materials Co., Ltd., type B, with a weight average molecular weight of 30 kDa to 50 kDa.

[0094] The polybenzimidazole used in the embodiment is poly(2,2'-(m-phenyl)-5,5'-benzimidazole), namely m-PBI, which is prepared by the following method:

[0095] 1. Raw material preparation: Weigh 10.7 g of 3,3',4,4'-biphenyltetramine (TAB) and 7.6 g of isophthalic acid (IPA), ensuring the molar ratio is 1:1. Prepare 100 mL of 85% polyphosphoric acid (PPA) as solvent and catalyst.

[0096] 2. Mix the reactants: Add TAB and IPA to 100 mL of PPA and stir well to form a uniform mixture.

[0097] 3. Heating polymerization: Heat the mixture to 200°C and keep it at this temperature for 6 hours. During the reaction, stir continuously to ensure uniform reaction.

[0098] 4. Cooling and separation: After the reaction is completed, the reaction mixture is cooled to room temperature. The reaction mixture is slowly poured into a large amount of deionized water (about 1L) to precipitate the polymer. The precipitate is collected by filtration and washed with deionized water several times until the filtrate is neutral. The washed precipitate is dried at 80°C for several hours to obtain m-PBI powder.

[0099] Pretreatment: In order to improve the polycondensation effect, PPA (100 ml) can be heated to 120° C. and maintained for 30 min under stirring and nitrogen atmosphere before the polycondensation reaction to remove moisture from polyphosphoric acid (PPA).

[0100] Example 1

[0101] 1. Preparation of ionic solvent membrane

[0102] (1) Preparation of sulfonated cellulose

[0103] First, 6.52 g of dried microcrystalline cellulose was weighed, 50 ml of 40% (v / v) sulfuric acid solution was added, and the solution was stirred at room temperature for 6 h. Then, the pH of the solution was adjusted to 7.0 with an aqueous NaOH solution to obtain sulfonated cellulose. The polymer was washed 5 times with deionized water and dried in vacuo at 70°C for 24 h before use.

[0104] (2) Membrane preparation

[0105] First, 0.15 g of the sulfonated cellulose obtained in step (1) was weighed and dissolved in 50 ml of DMAc. Then, 2.85 g of polybenzimidazole was added to the reaction system. The mass ratio of sulfonated cellulose to polybenzimidazole was 5:95, and the mass volume ratio (g / mL) of the total mass of sulfonated cellulose and polybenzimidazole to DMAc was 6%. The mixture was stirred and reacted at 130° C. for 6 h to obtain a casting solution. The casting solution was then cast on a glass plate and vacuum dried at 100° C. for 24 h to form a film.

[0106] (3) Base functionalization

[0107] The membrane obtained in step (2) was peeled off from the surface of the glass plate and placed in a 30 wt % KOH alkaline solution to complete the deprotonation process, thereby obtaining an ion solvent membrane.

[0108] 2. Performance Test

[0109] (1) Conductivity test

[0110] The membrane was immersed in a 30 wt% KOH aqueous solution for 24 hours, and then cut into a circle with a diameter of 3.5 cm. The initial conductivity of the circular sample was measured using a Gamry electrochemical workstation Reference 3000 impedance analyzer;

[0111] (2) Water contact angle test

[0112] First, you need to prepare the contact angle meter (JY-PHC), clean samples and test liquid water. Fix the sample on the sample stage of the instrument, adjust the camera and light source, and ensure that the sample surface is clearly visible. Use a syringe to add a small drop (1μL) of test liquid to the sample surface, immediately capture the drop shape through the camera, and use the instrument software to measure the contact angle formed by the drop and the sample surface. Record the results of each measurement, and take the average value of multiple measurements at different locations;

[0113] (3) Mechanical strength test

[0114] The membrane was cut into a 1.5 cm × 8 cm square and immersed in a 30 wt% KOH aqueous solution for 24 hours. The rectangular PBI membrane was taken out from the KOH aqueous solution after immersion, and the excess liquid on the surface was wiped off. The opposite ends of the short side of the PBI membrane were aligned in the fixture of the tensile testing machine to avoid lateral sliding or twisting during the stretching process. The tensile testing machine (ZQ-990L) was started and the m-PBI membrane was stretched at a preset rate of 10 mm / min until the tensile strength of the membrane was less than 0.05 MPa. The test was stopped.

[0115] (4) Alkaline electrolyzed water performance test

[0116] The prepared membrane was used as an ion solvent membrane and deprotonated in 30wt% KOH for 12 h. The nickel foam and Pt / C carbon cloth were used as cathodes and the Ni / Fe catalyst nickel foam was used as anode. They were all cut into squares of 3.0 × 3.0 cm for further use. The flow field area of ​​a single cell was 9 cm 2 The membrane, OER catalyst and HER catalyst were assembled into a battery together with a polytetrafluoroethylene insulating gasket. In the homemade electrolysis system, the battery was connected, and a 1M KOH aqueous solution was circulated at 60 ml / min. When the temperature reached 55°C, the current was 1000A / m 2 Activate for half an hour at a current density of , increase the current, record the corresponding potential, and plot the recorded potential and the corresponding current density data into a graph, with the horizontal axis being the potential (V) and the vertical axis being the current density (A / m²)

[0117] 3. Test Results

[0118] The obtained ion solvent membrane has a resistance of 23.3 mohm and a conductivity of 14.3 mS·cm at room temperature. -1 The contact angle between the membrane and water is 78.2°. In the wet state, the tensile strength of the membrane is 10.2MPa and the elongation at break is 181.8%. The membrane was tested for its alkaline water electrolysis performance. At 55°C and 1M KOH as anode and cathode catalyst, the current density reached 7000 A / m² at a voltage of 1.8V.

[0119] Example 2

[0120] (1) Preparation of sulfonated cellulose

[0121] First, 6.52 g of dried microcrystalline cellulose was weighed, 50 ml of 40% sulfuric acid solution was added, and after stirring at room temperature for 6 h, the solution was adjusted to pH 7.0 with NaOH aqueous solution to obtain sulfonated cellulose. The polymer was washed 5 times with deionized water and vacuum dried at 70°C for 24 h before use.

[0122] (2) Membrane preparation

[0123] First, 0.3 g of the sulfonated cellulose obtained in step (1) was weighed and dissolved in 50 ml of DMAc. Then, 2.7 g of polybenzimidazole was added to the reaction system. The mass ratio of sulfonated cellulose to polybenzimidazole was 10:90, and the mass volume ratio (g / mL) of the total mass of sulfonated cellulose and polybenzimidazole to DMAc was 6%. The mixture was stirred and reacted at 130°C for 6 h. The casting solution was then cast on a glass plate and vacuum dried at 100°C for 24 h to form a film.

[0124] (3) Base functionalization

[0125] The membrane obtained in step (2) was peeled off from the surface of the glass plate and placed in a 30 wt % KOH alkaline solution to complete the deprotonation process, thereby obtaining an ion solvent membrane.

[0126] The conductivity, water contact angle, mechanical strength and alkaline water electrolysis performance of the obtained ion solvent membrane were tested using the same test method as in Example 1. The test results are as follows:

[0127] The obtained ion solvent membrane has a resistance of 22.8 mohm and a conductivity of 14.6 mS·cm at room temperature. -1 The contact angle between the membrane and water is 70.0°. In the wet state, the tensile strength of the membrane is 7.6 MPa and the elongation at break is 225.4%. The membrane was tested for its alkaline water electrolysis performance. At 55°C and 1M KOH as anode and cathode catalyst, the current density reached 8000 A / m² at a voltage of 1.8V.

[0128] Example 3

[0129] (1) Preparation of sulfonated cellulose

[0130] First, weigh 6.52 g of dried microcrystalline cellulose, add 50 ml of 40% sulfuric acid solution, stir at room temperature for 6 hours, adjust the solution to pH 7.0 with NaOH aqueous solution to obtain sulfonated cellulose, wash the polymer with deionized water 5 times, and use it after vacuum drying at 70°C for 24 hours.

[0131] (2) Membrane preparation

[0132] First, 0.6 g of the sulfonated cellulose obtained in step (1) was weighed and dissolved in 50 ml of DMAc. Then, 2.4 g of polybenzimidazole was added to the reaction system. The mass ratio of sulfonated cellulose to polybenzimidazole was 20:80, and the mass volume ratio (g / mL) of the total mass of sulfonated cellulose and polybenzimidazole to DMAc was 6%. The mixture was stirred and reacted at 130°C for 6 h. The casting solution was then cast on a glass plate and vacuum dried at 100°C for 24 h to form a film.

[0133] (3) Base functionalization

[0134] The membrane obtained in step (2) was peeled off from the surface of the glass plate and placed in a 30 wt % KOH alkaline solution to complete the deprotonation process, thereby obtaining an ion solvent membrane.

[0135] The water contact angle and mechanical strength of the obtained ion solvent film were tested using the same test method as in Example 1. The test results are as follows:

[0136] The contact angle between the obtained ionic solvent membrane and water is 65.2°; in the wet film state, the tensile strength of the membrane is 8.4 MPa and the elongation at break is 228.6%.

[0137] Comparative Example 1

[0138] (1) Membrane preparation

[0139] First, 3 g of polybenzimidazole was weighed and added to 50 ml of DMAc to prepare a casting solution with a mass fraction of 6 wt%, and the mixture was stirred and reacted at 130 °C for 6 h. Then, the casting solution was cast on a glass plate and dried to form a film.

[0140] (2) Base functionalization

[0141] The membrane obtained in step (2) was peeled off from the surface of the glass plate and placed in a 30 wt % KOH alkaline solution to complete the deprotonation process, thereby obtaining an ion solvent membrane.

[0142] The conductivity, water contact angle, mechanical strength and alkaline water electrolysis performance of the obtained ion solvent membrane were tested using the same test method as in Example 1. The test results are as follows:

[0143] The obtained ion solvent membrane has a resistance of 27.5 mohm and a conductivity of 12.1 mS·cm at room temperature. -1 The contact angle between the membrane and water is 84.3°. In the wet state, the tensile strength of the membrane is 9.3 MPa and the elongation at break is 233.1%. The membrane was tested for its alkaline water electrolysis performance. At 55°C and 1M KOH as anode and cathode catalyst, the current density reached 6000 A / m² at a voltage of 1.8V.

[0144] Comparative Example 2

[0145] (1) Membrane preparation

[0146] First, 2.85 g of polybenzimidazole and 0.15 g of microcrystalline cellulose were weighed and added into 50 ml of DMAc. The mass ratio of microcrystalline cellulose to polybenzimidazole was 5:95, and the mass volume ratio (g / mL) of the total mass of cellulose and polybenzimidazole to DMAc was 6%. The mixture was stirred and reacted at 130 °C for 6 h. The casting solution was then cast on a glass plate and vacuum dried at 100 °C for 24 h to form a film.

[0147] (2) Base functionalization

[0148] The membrane obtained in step (1) was peeled off from the surface of the glass plate and placed in a 30 wt % KOH alkaline solution to complete the deprotonation process, thereby obtaining an ion solvent membrane.

[0149] The obtained ion solvent membrane has a resistance of 25.3 mohm and a conductivity of 13.2 mS·cm at room temperature. -1The contact angle between the membrane and water is 81.6°. In the wet state, the tensile strength of the membrane is 8.9MPa and the elongation at break is 223.4%. The membrane was tested for its alkaline water electrolysis performance. At 55°C and 1M KOH cathode and anode catalyst, the current density reached 5800A / m² at a voltage of 1.8V.

[0150] Table 1 shows the mechanical strength and contact angle with water of the ionic solvent membranes prepared in Example 1, Example 2, Example 3 and Comparative Example 1.

[0151] Table 1

[0152]

[0153] Table 1 shows the mechanical strength diagram and contact angle of the ion solvent membranes prepared in Example 1, Example 2, Example 3 and Comparative Example 1 and Comparative Example 2. The wet film properties were measured at room temperature. The ion solvent membrane in Example 1 had a tensile strength of 10.2 MPa, an elongation at break of 181.8%, and a contact angle of 78.2°; the ion solvent membrane in Example 2 had a tensile strength of 7.6 MPa, an elongation at break of 225.4%, and a contact angle of 70.0°; the ion solvent membrane in Example 3 had a tensile strength of 8.4 MPa, an elongation at break of 228.6%, and a contact angle of 65.2°; the ion solvent membrane in Comparative Example 1 had a tensile strength of 9.3 MPa, an elongation at break of 233.1%, and a contact angle of 84.3°; the ion solvent membrane in Comparative Example 2 had a tensile strength of 8.9 MPa, an elongation at break of 223.4%, and a contact angle of 81.6°. From the mechanical properties and contact angle data, it can be seen that with the introduction of sulfonated cellulose, its mechanical properties are improved, and with the increase of the introduced amount, the hydrophilicity increases.

[0154] Figure 2 The polarization curves of the ionic solvent membranes in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 in alkaline electrolysis of water are shown, wherein the horizontal axis is the current density and the vertical axis is the voltage. In the test environment of 55°C and 1M KOH, the membrane prepared in Example 1 maintains a current density of about 7000 A / m² at 1.8V; the membrane prepared in Example 2 maintains a current density of about 8000 A / m² at 1.8V; the membrane prepared in Comparative Example 1 maintains a current density of about 6000 A / m² at 1.8V; and the membrane prepared in Comparative Example 2 maintains a current density of about 5800 A / m² at 1.8V. It can be seen from the polarization performance data of Examples 1, 2 and Comparative Examples 1, 2 that as the amount of sulfonated cellulose introduced increases, the battery performance is improved, which indicates that the introduction of sulfonated cellulose promotes the transfer of ions in the membrane to a certain extent, improves the conductivity, and thus improves the battery performance.

[0155] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0156] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims, and the description and drawings may be used to interpret the content of the claims.

Claims

1. A method for preparing an ionic solvent membrane, characterized in that: The steps include: The sulfonated cellulose, an organic solvent and polybenzimidazole are mixed to prepare a casting solution, and the casting solution is heat-treated to form a film by casting; The membrane formed by casting is deprotonated to prepare the ion solvent membrane.

2. The preparation method according to claim 1, characterized in that: Calculated by feed amount, the mass ratio of the sulfonated cellulose to the polybenzimidazole is (5-20): (80-95).

3. The preparation method according to claim 1 or 2, characterized in that: In the casting solution, based on the feed amount, the mass volume ratio of the total mass of the sulfonated cellulose and the polybenzimidazole to the mass volume of the organic solvent is (5-10) g:100 mL.

4. The preparation method according to any one of claims 1 to 3, characterized in that Meet one or more of the following characteristics: The polybenzimidazole comprises one or more of poly(2,5-benzimidazole), poly(2,2'-phenyl-5,5'-benzimidazole), poly(2,2'-(m-phenyl)-5,5'-benzimidazole), pyridine bridged polybenzimidazole and poly(4,4'-diphenyl ether-5,5'-benzimidazole); The weight average molecular weight of the polybenzimidazole is 80 kDa to 100 kDa; The organic solvent comprises one or more of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.

5. The preparation method according to any one of claims 1 to 4, characterized in that The preparation method of the sulfonated cellulose comprises the following steps: mixing cellulose with a sulfonating agent to carry out a sulfonation reaction, and adjusting the pH value to 6.5-7.5 to prepare the sulfonated cellulose; Optionally, the method for preparing sulfonated cellulose satisfies one or more of the following characteristics: According to the feed amount, the ratio of the cellulose to the sulfonating agent is 1 g: (5-10) mL; The weight average molecular weight of the cellulose is 30 kDa to 100 kDa; The cellulose comprises one or more of microcrystalline cellulose, cellulose nanocrystals, bacterial cellulose and cellulose nanofibers; The sulfonating agent comprises one or more of sulfuric acid, chlorosulfonic acid, sulfur trioxide, aminosulfonic acid and sulfite; The sulfonating agent is added in the form of a sulfonating agent aqueous solution, and optionally, the sulfonating agent aqueous solution contains water and sulfuric acid, and the concentration of the sulfonating agent is 40% to 60%; The temperature for carrying out the sulfonation reaction is 5°C to 30°C; The sulfonation reaction is carried out for 6 h to 12 h.

6. The preparation method according to any one of claims 1 to 5, characterized in that Meet one or more of the following characteristics: The temperature for the heat treatment is 100°C to 130°C; The heat treatment is performed for 6 h to 24 h.

7. The preparation method according to any one of claims 1 to 6, characterized in that Meet one or more of the following characteristics: In the casting film forming step, the product obtained by heat treatment is cast on a substrate, and vacuum dried at 60° C. to 100° C. for 24 h to 36 h to form a film; In the step of performing the deprotonation, the deprotonation is performed using an alkali solution, and the alkali solution is a 20wt%~50wt% KOH solution.

8. An ionic solvent membrane, characterized in that It is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the ion solvent membrane according to claim 8 in alkaline water electrolysis or in an alkaline water electrolysis device.

10. An alkaline water electrolysis device, characterized in that: It comprises an alkaline electrolyzer system, wherein the alkaline electrolyzer system comprises the ionic solvent membrane of claim 8.